Characterizing low-contrast Galactic open clusters with Gaia Data Release 2 - Angelo, M S; Santos, J F C; Corradi, W J B (Monthly notices of the Royal Astronomical Society, 2020)
ABSTRACT In this study, we characterized 16 objects previously classified as faint or low-contrast Galactic open clusters (OCs). We employed parameters associated with the dynamical evolution of the OCs: the core (rc), tidal (rt) and half-mass (rhm) radii, age and crossing time (tcr). Relations among these parameters were exploited to draw some evolutionary connections. We also included 11 OCs with previous characterizations to provide wider coverage of the parameter space. The investigated sample spans a considerable range in age, log (t yr−1) ∼7.0–9.7, and Galactocentric distance, RG ∼ 6–11 kpc). Most of these OCs present solar metallicity. We employed Gaia Data Release 2 astrometry and photometry, and we selected member stars through a decontamination algorithm that explores the three-dimensional astrometric space (μα, μδ, ϖ) to assign membership likelihoods. Previous studies of most of these objects were based mostly on photometric information. All investigated OCs were proved to be real stellar concentrations. The relations among their parameters indicate a general disruption scenario in which OCs tend to be more concentrated as they evolve. Internal interactions sucessively drive OCs to develop more dynamically relaxed structures and make them less subject to mass loss due to tidal effects. Tidal radius tends to increase with RG in accordance with the strength of the Galactic tidal field. Besides, the correlation between rc and the dynamical ratio τdyn = age/tcr suggests two distinct evolutionary sequences, which may be a consequence of different initial formation conditions.